Estudo da adsorção de Cu(II) utilizando biocarvões de palha de café conilon - Oliveira, Yago Ricardo de (2018)
Among the various forms of environmental pollution, water pollution with heavy metals is a concern for researchers and government agencies involved in pollution control. Several researches on the adsorption of metal ions by biochar has been developed, whi